CSR as an Element of a Marketing Strategy – The Example of IKEA - Fabicka, Wioletta (The Best Practice of Marketing Management in Polish and International Enterprises: The Marriage of Science and Business – Case Studies, 2022)
The purpose of this paper is to explain the essence of the CSR concept and the validity of its practical implementation by large companies, the essence of corporate social responsibility in building the company's image and in the procurement process, and to present practical solutions for applying CSR in the marketing space. IKEA not only cares about its image through various CSR activities, but also uses CRM strategies in the context of marketing. These strategies are used not only to acquire new customers but also to build lasting business relationships based on mutual trust and shared values.